(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
We consider in this paper the analysis of a large set of malware and benign applications from the Android ecosystem. Although a large body of research work has dealt with Android malware over the last years, none has addressed it from a forensic point of view.